2018
DOI: 10.1016/j.aller.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of IL-31 levels and disease severity in children with atopic dermatitis

Abstract: IL-31 levels were significantly higher in AD patients compared to control group but irrelevant to the disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…This rate is lower than what is reported in the former study by Ricci et al [12], which was performed in a pediatric population with a similar number of cases. The previous studies conducted on pediatric AD patients in Turkey have also reported larger proportions of severe cases [13][14][15]. In the UK, however, the rates of mild, moderate, and severe AD in children reported to be 82, 12, and 6%, respectively; which are comparable to our results [16].…”
Section: Discussionsupporting
confidence: 89%
“…This rate is lower than what is reported in the former study by Ricci et al [12], which was performed in a pediatric population with a similar number of cases. The previous studies conducted on pediatric AD patients in Turkey have also reported larger proportions of severe cases [13][14][15]. In the UK, however, the rates of mild, moderate, and severe AD in children reported to be 82, 12, and 6%, respectively; which are comparable to our results [16].…”
Section: Discussionsupporting
confidence: 89%
“…This lack of significant association was also demonstrated by other studies. 29,30 However, a systematic review on IL-31 found serum IL-31 levels to correlate with pruritus intensity indicating that IL-31 is a key mediator in inducing pruritus. 31 The levels of interleukins in Ps did not correlate with disease or itch severity (measured by PASI/BSA, VAS, PGS) which indicates that other mediators in Ps pathogenesis are also implicated.…”
Section: Discussionmentioning
confidence: 99%
“…18,116,117 Curiously, despite some reports on the correlation of the ''itch cytokine,'' IL-31, with disease severity, 62,118 more evidence is accumulating on the lack of such correlation. 102,[119][120][121] Predictive biomarkers Tissue biomarkers predicting disease onset include TARC and IgE in the umbilical cords of newborns 122,123 and natural moisturizing factor levels in neonates' skin, 124 which are known to strongly correlate with transepidermal water loss, 23 another predictor of AD development in newborns. 125,126 Moisturizers can prevent AD in high-risk infants, 127 and were shown to alter skin microbiome and reduce skin pH in this population.…”
Section: Biomarkers That Failed To Show Consistent Correlation With Smentioning
confidence: 99%